2013
DOI: 10.1186/1754-6834-6-171
|View full text |Cite
|
Sign up to set email alerts
|

Attainable region analysis for continuous production of second generation bioethanol

Abstract: BackgroundDespite its semi-commercial status, ethanol production from lignocellulosics presents many complexities not yet fully solved. Since the pretreatment stage has been recognized as a complex and yield-determining step, it has been extensively studied. However, economic success of the production process also requires optimization of the biochemical conversion stage. This work addresses the search of bioreactor configurations with improved residence times for continuous enzymatic saccharification and ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…• Scott et al [73]: Attainable region analysis for continuous production of second-generation bioethanol.…”
Section: Discussionmentioning
confidence: 99%
“…• Scott et al [73]: Attainable region analysis for continuous production of second-generation bioethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Since a large number of the conceivable process configurations that can be obtained from the 2 28 possible combinations of the Boolean variables will not define feasible topologies, it is necessary to introduce a set of logic propositions relating the Boolean variables (ષሺሻ = ‫. )݁ݑݎܶ‬ Logic arguments can be incorporated to the superstructure by using the logical operators OR (∨), AND (∧), IF-THEN (⇒), XOR (exclusive or, ∨ ), NOT (¬) and IF AND ONLY IF (⇔).…”
Section: Economic Assessment and Objective Functionmentioning
confidence: 99%
“…However, a thorough comparison between process configurations is not possible due to an inexistent common framework of economic parameters and pretreatment conditions. Using the Attainable Region concept, Scott et al (2013) showed that for the saccharification and fermentation of PCS the reactor networks that minimize the residence time can be constructed using plug flow reactors and continuously stirred tank reactors, despite the complexity of the reaction networks and underlying kinetics. However, no solid separators were included in this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Though this semi-commercial process is able to produce bioethanol from unwanted biomass, it still requires optimisation and improvement to achieve economic success [13]. With this in mind, some researchers have employed AR techniques to analyse and improve the effectiveness of the bioreactor configuration to boost the production of bioethanol [14].…”
Section: Introductionmentioning
confidence: 99%